Lecturers’ challenges and confidence in implementing problem-based learning (PBL) in mathematic subject / Shamala Palaniappan, Muruga Chinniah and Oswald Timothy Edward - Palaniappan, P Siva Shamala; Chinniah, Muruga; Edward, Oswald Timothy (UiTM Cawangan Johor, 2024)
Mathematics is categorised as one of the most poorly taught, widely hated, and very hardly understood subjects in elementary schools. Previously, students taught in traditional mathematics education environments were preoccupied with exercises, rules, and equations that need to be learned but are of limited use in unfamiliar situations such as solving real-life mathematics projects. In contrast to conventional mathematics learning environments, a Problem-Based Learning (PEL) environment provides students with opportunities to develop their abilities to adapt and change methods to fit new situations. Therefore, the qualitative part is chosen to get explanations from lecturers who are teaching mathematics at Malaysian Public University. One-to-one interview sessions using semi-structured interviews were chosen. The findings of the inten1iew were arranged as follows: (1) lecturers' knowledge and experience of teaching maths to students; (2) students' capability to master the basic skills and knowledge of mathematics; (3) applying the PEL method to teach Math, its challenges and confidence level throughout the PEL session; and (4) lecturers' view towards the PEL challenges and usefulness applying in university level. The findings have revealed that teaching students using PEL positively affected student content knowledge and the development of skills such as collaboration, critical thinking, and problem-solving.